2019
DOI: 10.1093/mnras/stz1259
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropy of the Universe via the Pantheon supernovae sample revisited

Abstract: We employ the hemisphere comparison (HC) method and the dipole fitting (DF) method to investigate the cosmic anisotropy in the recently released Pantheon sample of type Ia supernovae (SNe Ia) and five combinations among Pantheon. For the HC method, we find the maximum anisotropy level in the full Pantheon sample is AL max = 0.361 ± 0.070 and corresponding direction (l, b) = (123.05A robust check shows the statistical significance of maximum anisotropy level is about 2.1σ. We also find that the Low-z and SNLS s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
34
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 73 publications
9
34
1
Order By: Relevance
“…Our result for the level of local anisotropy in Pantheon SN Ia is consistent with previous works that find null evidence against assumption of the isotropy (Andrade et al 2018;Zhao et al 2019b), although less stringent compared to global anisotropy constraint found by Soltis et al (2019). Analogously to eq.…”
Section: Anisotropy Considerationssupporting
confidence: 92%
“…Our result for the level of local anisotropy in Pantheon SN Ia is consistent with previous works that find null evidence against assumption of the isotropy (Andrade et al 2018;Zhao et al 2019b), although less stringent compared to global anisotropy constraint found by Soltis et al (2019). Analogously to eq.…”
Section: Anisotropy Considerationssupporting
confidence: 92%
“…The constraints obtained using the Pantheon dataset are in agreement with corresponding previous studies [5,42,68].…”
Section: Resultssupporting
confidence: 90%
“…The dipole directions in four cosmological models by using the Pantheon sample, and the dipole directions derived from the Union2 sample[39], Union2.1 sample[44] and JLA sample[50]. The star marks the axial direction to the plane of SDSS subsample[65]. The uncertainties of dipole directions could be found inTable 1. xxxxxx-9 towards (l, b) = (298.81 •+84.18 • −118.71 • , −19.80 •+14.07 • −63.25 • ), which is very close to the dipole direction in the dipole-modulated ΛCDM model.…”
mentioning
confidence: 99%